Glucocorticoids induce femoral head necrosis in rats through the HIF-1α/VEGF signaling pathway - HaoXu Tang; Lingli Yuan; ZhiYuan Xu; GuiFen Jiang; YingJie Liang; Ce Li; PengLin Ding; MinLong Qian (Scientific Reports)
Abstract Glucocorticoid-induced osteoblast dysfunction is the primary cause of steroid-induced osteonecrosis of the femoral head (SONFH). However, the specific underlying biological mechanisms of glucocorticoids’ effect on osteoblasts remain undetermined. Recently, the role of hypoxia-inducible factor 1-alpha (HIF-1α)/vascular endothelial growth factor (VEGF) signaling pathway in modulating bone formation has been studied. This study aimed to investigate the association and mechanism of the HIF-1α/VEGF signaling pathway in glucocorticoid-induced osteogenesis suppression in MC3T3-E1 cells. This study performed CCK8 and live/dead staining assays by stimulating MC3T3-E1 cells with varying dexamethasone (DEX) doses to elucidate its influence on cell proliferation and activity. Furthermore, Western blotting was carried out to investigate the expression of HIF-1α, runt-related transcription factor 2 (RUNX2), VEGF, osteopontin (OPN), and alkaline phosphatase (ALP) proteins to identify the optimal DEX concentration for simulating steroid-induced osteonecrosis cell models. Moreover, the osteogenic differentiation of cells was assessed by transfecting them with control or HIF-1α overexpression lentiviral vectors. Similarly, in vivo, hematoxylin and eosin staining, immunohistochemical staining, and micro-computed tomography were performed to validate in vitro results in the SONFH rat model. In vitro analyses revealed that a 10− 6 M concentration of DEX significantly suppressed cell viability and osteogenesis by decreasing HIF-1α and VEGF levels. Furthermore, HIF-1α upregulation increased osteogenic activity and VEGF expression in MC3T3-E1 cells. However, the HIF-1α antagonist 3-(5’-hydroxymethyl-2’-furyl) -1-benzylindazole (YC-1) indicated opposite effects in DEX-treated MC3T3-E1 cells. Moreover, SONFH femoral heads had reduced bone density, bone tissue content, and femoral head integrity, as well as increased bone cell lacunae, while decreased HIF-1α, OPN, VEGF, and ALP levels in bone tissue compared to normal rats. This study indicated that DEX suppresses osteoblast differentiation via the HIF-1α/VEGF pathway, thus promoting SONFH.